Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Bayesian Statistics 9 2011
DOI: 10.1093/acprof:oso/9780199694587.003.0004
|View full text |Cite
|
Sign up to set email alerts
|

Moment Priors for Bayesian Model Choice with Applications to Directed Acyclic Graphs*

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…The function m ( G ) in the multiple graphical model prior (Eqn. 4) provides an adjustment for the fact that the size of the space 𝒢 grows super-exponentially with the number P of vertices (Consonni and La Rocca, 2010). In this paper we follow Chen and Chen (2008); Scott and Berger (2010); Foygel and Drton (2013) and control multiplicity using the binomial correction mfalse(Gfalse)=i=1Ptrue(centerPcenter|Gi|true)1false[false|Gifalse|dmaxfalse]. Here d max is a fixed upper bound on the in-degree of vertices in G that encodes prior knowledge on the support of the graphical models (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The function m ( G ) in the multiple graphical model prior (Eqn. 4) provides an adjustment for the fact that the size of the space 𝒢 grows super-exponentially with the number P of vertices (Consonni and La Rocca, 2010). In this paper we follow Chen and Chen (2008); Scott and Berger (2010); Foygel and Drton (2013) and control multiplicity using the binomial correction mfalse(Gfalse)=i=1Ptrue(centerPcenter|Gi|true)1false[false|Gifalse|dmaxfalse]. Here d max is a fixed upper bound on the in-degree of vertices in G that encodes prior knowledge on the support of the graphical models (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, conventional model selection criteria for graphical models are often biased towards selecting more complex models (i.e. more edges), since there are typically very many models in which the data-generating model is nested; these models are also able to fit the data well (albeit with some coefficients close or equal to zero; Consonni and La Rocca, 2010). Consequently many more data are required to exclude more complex alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…Rossell et al (2013) found analogous τ for probit regression, and also considered learning τ either via a hyper-prior or minimizing posterior predictive loss (Gelfand and Ghosh, 1998). Consonni and La Rocca (2010) devised objective Bayes strategies. Yet another possibility is to match the unit information prior e.g.…”
Section: Non-local Priors As Truncation Mixturesmentioning
confidence: 99%
“…The parameter r is called the order of the density. Consonni and La Rocca (2010) proposed a similar class of prior densities for application to graphical models, though in their proposal the densities corresponding to Equation (2) are not proper.…”
Section: Introductionmentioning
confidence: 99%